Needs Analysis for The Development of Biology E-Modules Based on Project-Oriented Problem-Based Learning (POPBL) to Improve Students' Critical Thinking, Creativity, and Collaboration Skillss - Nurul Fajryani Usman; Nur Mustaqimah; Masra Latjompoh (Postgraduate, University of Mataram, 2024)
Education should not merely provide students with knowledge; rather, learning in educational institutions serves as a process for acquiring knowledge, skillss, and competencies. The researchers conducted preliminary research to identify teacher and students need in biology learning, as well as the levels of students' critical thinking skills, creative thinking skills, and collaboration skills. The instruments used in this research are questionnaire and test sheets. The data that has been collected will then be analyzed both quantitatively and qualitatively. The sample of the study are biology teacher and students in Fase D at SMAN 1 Kabila, Gorontalo Regency. Based on the analysis of student and teacher needs in biology learning, it can be concluded that the majority of students find the learning process difficult and monotonous. Although students exhibit good collaboration habits, 80% of them have never engaged in projects, and they desire the integration of technology into teaching materials. The results of critical and creative thinking ability tests indicate a